Effectiveness of EPS Bead Size and Cement Proportions on the Strength and Deformation of Light-Weighted Soil - Ali, S.; Yong, F.; Bhutto, A. H.; Jamil, F.; Khan, J. S.; Bhanbhro, R. (Engineering, Technology & Applied Science Research, 2022)
The current study investigates the deformation and strength of Light-Weighted Soil (LWS) comprised of silt, Expanded Polystyrene (EPS) beads, cement, and water. The EPS bead sizes employed in this study are 4, 5, and 6mm in diameter with densities of 0.011, 0.009, and 0.006g/cm3 and cement concentrations of 10% and 15%. The effects of different EPS bead sizes and cement proportions on the mechanical properties (strength and deformation) of LWS are evaluated by Unconfined Compression Strength (UCS) tests. The findings show that the EPS bead sizes significantly impact the strength and deformations of the LWS. The smaller the EPS bead size, the higher the observed strength, but, on the other hand, bigger EPS bead sizes have lower strength and higher ductility. It was also revealed that the strength of LSW is entirely dependent on the cement concentration. High cement content in the LWS has more strength and brittleness, but it is more prone to deformation. The cost can be decreased by increasing the EPS bead size, and thus the prescription of mixed soil can be enhanced. The use of EPS beads with a diameter of 4-6mm is recommended in the construction process, especially in backfill for retaining walls. Each EPS bead size provides advantages in different context, depending on engineering applications and field conditions.